The Intensive Language Teaching Program in Teaching Arabic Language to The Islamic Center Group “Abdullah Ghanem Al-Shamael” Ponorogo Held at the Darussalam Gontor University - Yoke Suryadarma; Ahmad Muthi Baiquni (Educan : Jurnal Pendidikan Islam, 2018)
This research is the implementation of the intensive language program in the teaching of the Arabic language of the Islamic Center Group "Abdullah Ghanim As-Syamail" Ponorogo. The Islamic Center is the intensive language program in the teaching of the Arabic language, which was implemented by the Department of Arabic Language Education Faculty of Education, University of Darussalam Gontor, supervised by the faculty of Arabic language teaching department. The implementation of this program is confined to one point on reading comprehension. This program aims to reveal implementation of this intensive language program and degree of confiction. The adoption of this research on the field curriculum to know the implementation of the intensive language program in teaching Arabic in the field of research. Data in this study are derived from the observation, interview and written documents. The result of this research was the planning of the intensive language program in the teaching of the Arabic language and the method of implementation of this program and the evaluation of this program of tribal evaluation and post-evaluation.